The development of the parental feeding behaviours questionnaire for Indonesian parents with toddlers: preliminary result - Lusmilasari, Lely; Chaiyawat, Waraporn; Rodcumdee, Branom (International Journal Of Community Medicine And Public Health, 2017)
Background: An accurate assessment of parents feeding behaviors is needed to determine current feeding behaviors of parents that are closely associated with the fulfillment of their toddlers’ nutritional needs. This study aims to develop an instrument, the Parental Feeding Behaviors Questionnaire (PFBQ), for measuring feeding behaviors of Indonesian parents with toddlers. Methods:An initial seventy-item instrument was developed after a comprehensive literature review which was submitted to be reviewed by six experts to evaluate the content validity of the PFBQ. The pre-test study was conducted by a convenience sampling of 30 parents who have toddlers both in urban and rural area in Yogyakarta, Indonesian for the first draft of 80-item instrument. Initial item analysis was measured using inter-item correlation, inter-total correlation and Cronbach’ s alpha. Results: The PFBQ is the ways that Indonesian parents do that consist of three dimensions which are to provide healthy food, provide pleasant eating environment for their toddlers, as well as enhance the toddlers’ good eating behaviors. The score of the Content Validity Index of the PFBQ is I-CVI (.83-1.00) and S-CVI (.98). Most of the items have acceptable inter-item correlation value (>.3). There are 56 items that are correlated with the total scores which range .30 to .62. The value of Cronbach’s alpha is .94. Conclusions:The PFBQ shows initial reliability and validity to assess the parental feeding behaviours for their toddlers. However, further testing is needed to test construct validity and reliability with a large sample for the improvement of the instrument.